Adverse Impact of Supernumerary X Chromosome on Anthropometric, Endocrinological, and Metabolic Parameters and Cardiac Function in Males - Grinspon, Romina (2024)
Klinefelter syndrome is the most frequent sex chromosome polysomy, with a prevalence of 1 to 2 per 1000 (1). Most subjects are diagnosed in adulthood for infertility. During childhood the diagnosis usually goes unnoticed since prepubertal boys do not exhibit specific physical features. The clinical manifestations associated with Klinefelter syndrome (47,XXY) are widely described and mainly include hypergonadotrophic hypogonadism beginning in mid-puberty (2), clinically presenting with low testicular volume, gynecomastia, infertility, osteopenia, and metabolic syndrome. Other subtle manifestations present before puberty are not associated with hypogonadism and include learning disabilities, delayed speech development, and minor congenital malformations such as clinodactyly, cleft palate, and inguinal hernia. A smaller proportion of males have other sex chromosome polysomies: 48,XXYY and 48,XXXY are present in 1:17 000 to 1:50 000 male births and the incidence of 49,XXXXY is 1:85 000 to 1:100 000 male births (3); however, their clinical characterization is more limited, probably due to their low frequency.